Dietary iron intake in adolescent women in educational institutions - Vila, Mabel (2008)
Introduction: Iron deficiency anemia is a public health problem. The low dietary intake of iron is one of its causes. Objective: To determine the dietary iron intake in adolescent women. Design: Descriptive, cross type study. Setting: Educational Institutions in the district of Ancon, Lima. Participants: Three hundred and fifty-five adolescent high school female students in Ancon chosen at random. Interventions: Previous informed consent, a semi-quantitative food and beverage frequency questionnaire was given. Main outcome measures: Daily dietary iron intake. Results: Adolescents average age was 14 ± 1,69 years. The median dietary iron intake was 10,4 mg (quartile 1 = 9 mg / day, quartile 3 = 12,1 mg / day), and the median adequacy, 38,4% (quartile 1 = 33,45%; quartile 3 = 45,56%); 86,8% of all adolescents did not satisfy even 50% of their recommended daily iron intake. The high bioavailability iron represented one-tenth of the total iron ingested. Bread and rice were the foods that provided more iron to the diet. Conclusions: We found inadequate iron intake in 86,8% of adolescents evaluated, and low high bioavailability iron intake.